Pemetaan Lanskap Penelitian Fungsi Hash dan Secure Hash Algorithm: Studi Bibliometrik Menggunakan Biblioshiny - Saputra, Imam; Siregar, Annisa Fadillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Hash functions and secure hash algorithms are vital components in modern cybersecurity, essential for ensuring data integrity and authenticity. With the development of new attacks and the emergence of novel applications, the research landscape in this field has become highly dynamic and complex. This study aims to map the research landscape related to hash functions and secure hash algorithms using a comprehensive bibliometric study approach. Publication data comprising 494 journal and conference proceeding articles were collected from the Scopus database using a specific query. Bibliometric analysis was performed using Biblioshiny software, covering basic characteristics analysis, keyword co-occurrence, citation analysis (most cited works, intellectual structure), collaboration, thematic mapping, and thematic evolution. The results show significant publication growth over time, identifying key contributors (countries, institutions, authors) as well as the most relevant publication sources. Keyword analysis and thematic mapping revealed dominant research themes and clusters (e.g., core cryptography, hardware implementation, image security applications, potential in the healthcare sector), while citation analysis highlighted the most influential articles and authors forming the knowledge foundation. Thematic evolution demonstrated a shift in research focus from fundamental algorithms towards broader application exploration and related techniques in more recent periods. This study provides a comprehensive data-driven overview of the structure, trends, and dynamics of research on hash functions and secure hash algorithms. These findings contribute to understanding the status of this field and identify potential areas for future research, assisting researchers and practitioners in navigating the extensive literature.